New Drug Delivery System Based on Nystatin Loaded Poly(DL-lactide-co-caprolactone) Microspheres - Kassab, R.; Yammine, P.; Moussa, D. (Asian Journal of Chemistry, 2011)
In this study, the usage of biodegradable polymer for microencapsulation of nystatin using solvent evaporation technique is investigated. For this purpose, poly(DL-lactide-co-caprolactone) microspheres containing nystatin were prepared with different drugs masses. The microspheres were then evaluated for particle size, morphology, Fourier transform-infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) studies, percentage yield, drug entrapment, stability and in vitro studies. Optical microscopy revealed that the microspheres have a spherical shape. The drug entrapment increased with increasing drug content up to a particular concentration. FT-IR and DSC showed that there was no chemical interaction between the drug and the polymer. Stability study showed no appreciable difference concerning the degradation of the microspheres after 60 days of storage. The in vitro release study showed that nystatin release from all the formulations was slow for one week followed by an increase to reach 90 % for the formulation containing the highest quantity of nystatin.